2012
DOI: 10.1021/jm201482p
|View full text |Cite
|
Sign up to set email alerts
|

Radiolabeled Cyclosaligenyl Monophosphates of 5-Iodo-2′-deoxyuridine, 5-Iodo-3′-fluoro-2′,3′-dideoxyuridine, and 3′-Fluorothymidine for Molecular Radiotherapy of Cancer: Synthesis and Biological Evaluation

Abstract: Targeted molecular radiotherapy opens unprecedented opportunities to eradicate cancer cells with minimal irradiation of normal tissues. Described in this study are radioactive cycloSaligenyl monophosphates designed to deliver lethal doses of radiation to cancer cells. These compounds can be radiolabeled with SPECT- and PET-compatible radionuclides as well as radionuclides suitable for Auger electron therapies. This characteristic provides an avenue for the personalized and comprehensive treatment strategy that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 73 publications
0
32
0
Order By: Relevance
“…The effect of AE-emitters on cell survival was first studied with molecules that can be incorporated in to the DNA, such as 125 I-UDR. These studies provided valuable knowledge that illuminated the inverse relationship between AE-emitter distance to the DNA and DNA damage and cell kill ( Kortylewicz et al, 2012 ). Since then, several small molecule DNA intercalators have been proposed as nuclear-targeting agents for AE-emitting radionuclides, such as radiolabeled derivatives of acridine orange ( Pereira et al, 2017 ), pyrene ( Häfliger et al, 2005 ; Reissig et al, 2016 ), doxorubicin ( Imstepf et al, 2015 ), and daunorubicin ( Fondell et al, 2011 ).…”
Section: Subcellular Targets For Radionuclide Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of AE-emitters on cell survival was first studied with molecules that can be incorporated in to the DNA, such as 125 I-UDR. These studies provided valuable knowledge that illuminated the inverse relationship between AE-emitter distance to the DNA and DNA damage and cell kill ( Kortylewicz et al, 2012 ). Since then, several small molecule DNA intercalators have been proposed as nuclear-targeting agents for AE-emitting radionuclides, such as radiolabeled derivatives of acridine orange ( Pereira et al, 2017 ), pyrene ( Häfliger et al, 2005 ; Reissig et al, 2016 ), doxorubicin ( Imstepf et al, 2015 ), and daunorubicin ( Fondell et al, 2011 ).…”
Section: Subcellular Targets For Radionuclide Therapymentioning
confidence: 99%
“…DeSombre and others subsequently evaluated various radiolabeled agents for the treatment of cancer, including 123 I- and 111 In-labeled analogs of estrogen and diethylstilboestrol, a non-steroid ER agonist ( DeSombre et al, 2000 ; Yasui et al, 2001 ; Fischer et al, 2008 ; Vultos et al, 2017 ). Kortylewicz et al (2012) developed an interesting hybrid molecule that exploits dual AR targeting and S-phase specific cell kill by linking 5α-dihydrotestosterone with 5-radioiodo-2′-deoxyuridine. They showed that this drug is initially trapped in the cytoplasm but associates exclusively with nuclear DNA after 24 h. A relatively low dose of radioactivity resulted in a reduction in clonogenic survival dependent on the expression of AR ( Kortylewicz et al, 2012 ; Han et al, 2014 ).…”
Section: Subcellular Targets For Radionuclide Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…This target compound was obtained through the typical stannylation of the iodide by hexamethylditin in the presence of triethylamine catalyzed by bis-(triphenylphosphine) palladium(II) dichloride using our previously described procedures. [20][21][22][23] Stannylations were carried out under nitrogen in refluxed MeCN using crude iodide 2 contain-ing~7% of 1. The final purification of the stannane was accomplished on the HPLC system equipped with a semipreparative column after numerous injections of a crude product.…”
Section: Resultsmentioning
confidence: 99%
“…Thymidine kinase 1 (TK1) and thymidine phosphorylase (TYMP) are key cytosolic thymidine salvage enzymes and targeted by anticancer thymidine therapeutics [ 1 - 5 ]. Two isoforms of TKs have been identified in cells, TK1 in cytosol and TK2 in mitochondria, which convert thymidine, 2’-deoxyuridine and 5-substiuted-2’-deoxyuridine or 2’-deoxycytidine (TK2) to the 5’-monophosphate form [ 2 - 4 ]. Low levels of TK1 are generally expressed in normal adult cells while high levels of TK1 are characteristic of cancer cells [ 6 - 9 ].…”
Section: Introductionmentioning
confidence: 99%